EFEITO DE SURFACTANTES NA ESTABILIDADE DE COMPOSTOS DE USO TERAPEUTICO - De Oliveira, A. G. (My University, 1990)
A critical revision of literature as regards to the drug stability in the presence of surfactants were realized. The functional groups envolved in the drug decomposition were used to the development of the discussion. The analysis indicated that the detergent effect can be used to control the rates and mechanisms of drug decomposition and to obtain specific information about the drug reactivity in the environment of pharmacological action.
Surfactants effect on the stability of therapeutic use compounds
Keywords: acetylsalicylic acid; amide; ampicillin; antiinfective agent; benzocaine; benzodiazepine derivative; beta lactam antibiotic; bile salt; carboxylic acid derivative; cephalosporin derivative; cetrimide; cetylpyridinium salt; chloramphenicol; chlordiazepoxide; chlorpromazine; clonazepam; clopenthixol; diazepam; diethazine; dodecyl sulfate sodium; dodecyltrimethylammonium chloride; drug metabolite; ester; flupentixol; functional group; homatropine; indometacin; methylprednisolone; oxazepam; penicillin derivative; penicillin g; phenothiazine derivative; procaine; propicillin; prostacyclin; salicylic acid derivative; surfactant; tetracaine; unclassified drug; catalysis; drug degradation; drug stability; hydrolysis; micelle; phototoxicity; reaction analysis